2019
DOI: 10.1136/bmjopen-2019-031856
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer incidence and mortality in the Baltic states, Belarus, the Russian Federation and Ukraine

Abstract: BackgroundProstate cancer incidence varies internationally largely attributable to differences in prostate-specific antigen (PSA) use. The aim of this study was to provide the most recent detailed international epidemiological comparison of prostate cancer incidence and mortality in six north-eastern European countries (Belarus, Estonia, Latvia, Lithuania, the Russian Federation and Ukraine).MethodsThe number of incident prostate cancer cases was obtained from the countries national cancer registries. Prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…These changes were followed by a mortality decrease by 37% from baseline prostate cancer mortality level [ 6 ]. In Lithuania, there was observed increasing mortality trend from 1985 to 2006 by 3.6% annually and decreasing mortality trend from 2006 by 1.4% annually [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes were followed by a mortality decrease by 37% from baseline prostate cancer mortality level [ 6 ]. In Lithuania, there was observed increasing mortality trend from 1985 to 2006 by 3.6% annually and decreasing mortality trend from 2006 by 1.4% annually [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This program works in the setting of nationwide PSA test-based screening and 70% of men aged 50 years to 74 years have participated in the prostate cancer program at least once in the first 10 years of the screening. During the screening period, prostate cancer incidence exhibited a dramatic increase in incidence and reached 279.33 cases per 100,000 (from 69.32 cases per 100,000 in 2000, European standard), with slowly decreasing prostate cancer mortality since 2007 [ 14 ]. However, all-cause and other cause mortality risk differences after implementation of prostate screening in Lithuania have never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a rapid incidence peak since the start of screening program, followed by a decrease thereafter. In Lithuania, PSA became available in 2000, and in 2006, a nationwide PSA-based prostate cancer early detection program was started [7]. Since the start of the program, in the period between 2006–2010 around 72–78% of the total eligible male population received at least one PSA test [5].…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, these incidence changes led to a decrease in the incidence rate. Mortality in Lithuania had been continuously growing, however, in 2006 mortality started to decrease by 1.4% annually [7]. This decrease is unlikely attributable to the success of the early effects of EPCDP, as the start of decrease is the same as the start of the program.…”
Section: Introductionmentioning
confidence: 99%
“…Lithuania is an interesting country to study the interaction between diabetes and PCa. In a recent publication comparing data from Belarus, Estonia, Latvia, Lithuania, the Russian Federation and the Ukraine [7], it was shown that the highest incidence of PCa was found in the Baltic States such as Lithuania and low incidence in Belarus, the Russian Federation and Ukraine. Furthermore, the annual percentage changes (APC) showed the largest increase in Lithuania.…”
Section: Impact Of Diabetes and Metformin Use On Prostate Cancermentioning
confidence: 99%